Hubungan Antara Penggunaan Kontrasepsi Hormonal Dengan Produksi Asi Pada Ibu Menyusui Di Bps Tatik S, Desa Ngasem, Kecamatan Ngasem, Kabupaten Kediri - Dian Permatasari; Galih Tri Mardaningrum (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2018)
The suckling mother who do not wanted pregnancy again, of course need savely contraception, which not disturb suckle process nor influence production of ASI. The reason is to arrange wanted child distance and amount, lessening risk infected by disease of sexual relation. Choosen contraception for the suckling mother must precisely, because if do not, it’s will influence production of ASI, especially if her choose to use hormonal contraception which contain estrogen hormonal, this matter will influence production of ASI which finally causes the baby is not maximal get ASI, especially Exclusive ASI. This research is correlation analitic research which want to know correlation between the hormonal contraception using and breastfeeding production for the suckling mother in BPS Tatik S, Ngasem, Kediri in 2009, use cross sectional approach. Population and sample in this research is suckling mother who use contraception hormonal in BPS Ny. Mustardiyah year 2009. Sampel account is about 49 people. This research use non probability sampling, that is consecutive sampling. The hypothesis test use chi-square because the variable are nominal and nominal scale with α 0,05. Based on the research result, all of the suckling mother use hormonal contraception, the breastfeeding production of the some of all the suckling mother are decrease, and there is a correlation between the hormonal contraception using and breastfeeding production for the suckling mother in BPS Tatik S, Ngasem, Kediri in 2009.